2015
DOI: 10.3762/bjoc.11.55
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific RNA cleavage by PNA conjugates of the metal-free artificial ribonuclease tris(2-aminobenzimidazole)

Abstract: SummaryTris(2-aminobenzimidazole) conjugates with antisense oligonucleotides are effective site-specific RNA cleavers. Their mechanism of action is independent of metal ions. Here we investigate conjugates with peptide nucleic acids (PNA). RNA degradation occurs with similar rates and substrate specificities as in experiments with DNA conjugates we performed earlier. Although aggregation phenomena are observed in some cases, proper substrate recognition is not compromised. While our previous synthesis of 2-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 21 publications
0
38
0
2
Order By: Relevance
“…It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51]. Effective cleavage of complementary substrates was also demonstrated for tris(2-aminobenzimidazole) ribonuclease conjugated to PNA oligomers [49]. It is important to emphasize though that none of the above developments have been demonstrated against clinically relevant RNA sequences, and most of the studies in this area have been carried out so far using either short, linear RNA sequences or model RNAs (e.g.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51]. Effective cleavage of complementary substrates was also demonstrated for tris(2-aminobenzimidazole) ribonuclease conjugated to PNA oligomers [49]. It is important to emphasize though that none of the above developments have been demonstrated against clinically relevant RNA sequences, and most of the studies in this area have been carried out so far using either short, linear RNA sequences or model RNAs (e.g.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Over the last couple of decades, some progress has been achieved in the field of designing siteselective artificial ribonucleases [42][43][44][45][46][47][48][49][50][51][52][53][54]. It was shown that short peptides, containing either alternating leucine and arginine residues or imidazole-based catalytic groups, conjugated to antisense oligonucleotides targeting tRNA, were able to hydrolyze linkages adjacent to an oligonucleotide-binding site without involvement of exogenous species such as metal ions, enzymes or cofactors (e.g., RISC, RNase H) [42,44,45,47,50,51].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This concept enabled the development of artificial enzymes capable of cleaving target RNA sequences with turnover [ 20 , 21 , 22 ]. Previous efforts have also resulted in the development of peptide nucleic acid-based artificial nucleases (PNAzymes) [ 23 , 24 , 25 , 26 ]. PNAzymes using Cu 2+ as a co-factor were shown to act as RNA restriction enzymes with high site selectivity and half-lives of cleavage down to 15 to 30 min, at a 1:1 ratio of PNAzyme to RNA [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective catalysts that are based on metal ions [17][18][19][20][21][22][23], guanidines or polyamines [24][25][26][27], peptide conjugates [28][29][30][31][32], and deoxyribozymes [33,34] have been described. Starting from heterocyclic guanidine analogs [35], we have investigated the conjugates of tris(2-aminobenzimidazoles) and different types of oligonucleotides, such as DNA [36], PNA [37,38], or DNA-LNA mixmers [39], which were shown to act as sequence-specific metal-free RNA cleavers. Product inhibition prevented multiple turnover when the catalyst was attached to a terminal position of the conjugates and the reaction was run under isothermal conditions, because the number of base pairs in the conjugate-substrate hybrid does not change in the cleavage step [36].…”
Section: Introductionmentioning
confidence: 99%